Study of the improvement of mechanical properties in a low carbon steel ASTM 615a grade 60 due to the formation of tempered martensite (LACCEI, 2024)
This research work consists of studying the improvement of mechanical properties through heat treatments, especially hardness and impact resistance in ASTM 615a grade 60 corrugated steel. 12 samples were prepared, one without treatment and the others with quenching and tempering heat treatments, different parameters such as austenitization temperature, tempering temperature and tempering time were evaluated. After evaluating the hardness and toughness, it was possible to improve the hardness in the 11 samples and the toughness was maintained at values close to the sample without treatment. In addition, a metallographic analysis and a microstructural analysis were made, where the presence of martensite could be observed, which is a mestastable phase of steels, the presence of martensite may be the cause of the increase in the hardness of the material. The quality of the steel obtained could be used as grinding balls in mineral concentrator machines due to its hardness.